Spatio-temporal distribution and source partitioning of formaldehyde over Ethiopia and Kenya. (15th September 2020) - Liu, Yang; Tang, Zhipeng; Abera, Temesgen; Zhang, Xuezhen; Hakola, Hannele; Pellikka, Petri; Maeda, Eduardo
Abstract: Understanding the local sources of atmospheric formaldehyde (HCHO) is a key step in accurately determining the inversion of biogenic volatile organic compounds (BVOCs). This study aims to clarify the main sources and emission patterns of local total HCHO column densities over Ethiopia and Kenya. Between 2005 and 2015, the total monthly HCHO varied from 3.7 × 10 15 molecules/cm 2 to 7.7 × 10 15 molecules/cm 2 . Monthly HCHO showed a strong seasonal pattern with annual peaks on March, July (small peak) and October, which well matched with the rainy seasons in Ethiopia and Kenya. Natural sources contributed 36% to the total HCHO in the study area. Grassland and savannas showed high column densities in the long rainy season starting from March, with the monthly average emission value of 5.6 × 10 15 molecules/cm 2 . Multiple regression result showed that vegetation contributed 3.5 × 10 13 molecules/cm 2 to monthly HCHO, with grassland and forest in eastern Kenya and the boundary of Ethiopia and Kenya were the main contributors in these regions. Biomass burning and methane contributed to HCHO emission in the western and northern Ethiopia with a magnitude of 1.4 × 10 14 molecules/cm 2 and 6.2 × 10 16 molecules/cm 2 per month, respectively. Economic activities showed negative response to HCHO columns, except over the two small-scale regions of Addis Ababa City and Nairobi City. This study quantified the HCHO from various sources and suggested that natural sources produce more HCHO than anthropogenic sources over Ethiopia and Kenya. Highlights: High column densities of HCHO over grassland and savanna areas compared to other land covers. Natural sources contributed 36% of the total HCHO in western Ethiopia and southern Kenya. Biomass burning and vegetation was the top HCHO contributor in western Ethiopia and eastern Kenya, respectively. Economic activities explain the HCHO trend in Addis Ababa City and Nairobi City better than other sources.